Toolbox for the Computation of 2D Fourier Transforms in Polar Coordinates via Maple. Issue 1 (5th February 2015) - Dovlo, Edem; Baddour, Natalie
The Fourier transform is one of the most useful tools in science and engineering and can be expanded to multi-dimensions and curvilinear coordinates. A toolbox of functions for the computation of two dimensional Fourier transforms in polar coordinates with symbolic computer algebra (Maple) was developed. The implementation of the 2D Fourier transform in polar coordinates within the toolbox is a combination of two significantly simpler transforms. A modular approach is used along with the idea of lookup tables to help avoid the issue of indeterminate results when attempting to directly evaluate the transform. This concept helps prevent unnecessary computation of already known transforms thereby saving memory and processing time.